2012
DOI: 10.3109/10717544.2012.657717
|View full text |Cite
|
Sign up to set email alerts
|

Novel tamarind seed polysaccharide-alginate mucoadhesive microspheres for oral gliclazide delivery:in vitro–in vivoevaluation

Abstract: Novel tamarind seed polysaccharide (TSP)-alginate mucoadhesive microspheres were prepared using TSP and alginate as blend in different ratios with different calcium chloride (CaCl 2 ) concentration as a cross linker by ionotropic gelation. The prepared microspheres were of spherical shape having rough surfaces, and average particle sizes within the range of 752.12 ± 6.42 to 948.49 ± 20.92 µm. The drug entrapment efficiency of these microspheres were within the range between 58.12 ± 2.42 to 82.78 ± 3.43% w/w. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…All experiments were done in triplicate (n=3). The swelling index of the microcapsules was calculated from the following formula (16,17):…”
Section: Characterisation Of Pb-loaded Microcapsulesmentioning
confidence: 99%
“…All experiments were done in triplicate (n=3). The swelling index of the microcapsules was calculated from the following formula (16,17):…”
Section: Characterisation Of Pb-loaded Microcapsulesmentioning
confidence: 99%
“…The capability of FP1-FP12 is to protect the body from weight loss as a result of to reduce hyperglycemia. The outcomes of this study showed that synthesized hydroxamic acid derivatives (FP1-FP12) have a hypoglycemic effect in streptozotocin-induced diabetic rats [28][29][30][31][32][33][34][35][36][37][38]. The antihyperglycemic effects of FP1-FP12 may be mediated through an increase in insulin secretion, the inhibition of gluconeogenesis and glycogenolysis and/or protection of pancreatic β-cells from streptozotocin and glucose-induced oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…In another investigation, the same group developed and evaluated tamarind seed polysaccharide-alginate mucoadhesive microspheres containing gliclazide by varying ratios of polymer-blends and calcium chloride concentrations in cross-linking solution through ionotropicgelation. 96 The drug entrapment efficiencies in these microspheres were 58.12 ± 2.42 to 82.78 ± 3.43% w/w; whereas microparticle sizes were 752.12 ± 6.42 to 948.49 ± 20.92 μm. These microspheres showed prolonged in-vitro release of gliclazide over 12 h. Both the metformin HCl-loaded beads and gliclazide-loaded microspheres made of tamarind seed polysaccharidealginate blends showed good ex-vivo mucoadhesivity with the biological membrane in wash-off test.…”
Section: Mucoadhesive Microparticles/beadsmentioning
confidence: 99%
“…93,94 The same research group has developed also tamarind seed polysaccharide-blended alginate mucoadhesive beads and microspheres through ionotropic-gelation. 95,96 Mucoadhesive beadscomposed of tamarind seed polysaccharide-alginate blends for oral delivery of metformin HCl were developed and optimized. 95 The optimized beads exhibited 94.86 ± 3.92% drug encapsulation efficiency and average diameter of 1.24 ± 0.07 mm.…”
Section: Mucoadhesive Microparticles/beadsmentioning
confidence: 99%
See 1 more Smart Citation